Iron-cobalt-nickel-chromium oxide nano material as well as preparation method and application thereof
By using iron-cobalt nickel-chromium oxide nanomaterials and bipolar membrane technology in the electrolytic seawater hydrogen production device, the problems of easy precipitation and poor stability of the electrode are solved, efficient and stable hydrogen and oxygen generation are achieved, and cost is reduced.
Patent Information
- Application Number
- CN202411981931.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The electrodes in the electrolytic seawater hydrogen production device are prone to precipitation, have poor operating stability, and the existing spacer materials have not yet been applied on a large scale and are still in the laboratory research stage.
Iron-cobalt nickel-chromium oxide nanomaterials are used as the cathode and anode material, combined with bipolar film technology, nanomaterials are prepared by electrodeposition and calcination to achieve high-efficiency hydrogen evolution and oxygen evolution within a wide pH range.
The stable operation of the hydrogen production process of electrolytic seawater is achieved, the Faraday efficiency exceeds 90%, and the cost is reduced and the use of precious metals is avoided.
Smart Images

Figure CN119877001A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy, and in particular to an iron-cobalt-nickel-chromium oxide nanomaterial, a preparation method and an application thereof. Background Art
[0002] Seawater resources are abundant and have high ionic conductivity. When used for electrolysis of seawater to produce hydrogen, no additional ions need to be added, which can save costs. However, since the redox potential of the chlorine evolution reaction (chlorine: 1.36V) is close to that of the oxygen evolution reaction (1.23Vvs RHE), the chlorine evolution reaction in seawater can compete with the oxygen evolution reaction to generate chlorine, thereby causing corrosion to the anode, resulting in the electrolysis of seawater to produce hydrogen. The operation cannot be stable. Therefore, it is crucial to improve the direct seawater electrolysis to produce hydrogen by limiting the oxidation reaction of chloride ions in seawater at the anode through the use of suitable spacer materials. Currently, a variety of spacer materials have been used for direct seawater electrolysis to produce hydrogen. For example, a Chinese patent entitled "A system and method for producing hydrogen from seawater using a hybrid alkaline and proton exchange membrane" uses a proton exchange membrane to separate the anode and cathode liquids; a Chinese patent entitled "A direct seawater hydrogen production device with a conductive hydrophobic membrane and a method for producing hydrogen from seawater using the same" uses an integrated conductive hydrophobic membrane to combine seawater desalination and water electrolysis hydrogen production technologies; a Chinese patent entitled "A PBI proton exchange membrane electrolysis module and a seawater electrolysis hydrogen production device" modularizes the anode and cathode catalysts and membranes to achieve hydrogen production from seawater by electrolysis, but the above-mentioned spacer materials have not yet been applied on a large scale and are still in the laboratory research stage.
[0003] The bipolar membrane is a composite membrane of anions and cations. It can achieve efficient dissociation of water while not allowing any ions to pass through. As a spacer material, it can effectively isolate the cathode and anode solutions in the direct electrolysis of seawater to produce hydrogen, thereby eliminating the side reaction of chloride ions at the anode and improving the efficiency of seawater electrolysis. A properly designed bipolar membrane seawater electrolysis device, combined with an asymmetric electrolyte feed, can not only limit the diffusion of chloride ions to the anode, but also provide an alkaline environment to maintain the anode and an acidic environment to maintain the cathode, inhibiting the precipitation of seawater in the cathode chamber, thereby achieving stable hydrogen evolution. In addition, the rate of water dissociation in the bipolar membrane is much greater than the rate of water electrolysis. Therefore, the excess hydrogen ions and hydroxide ions generated by water dissociation in the bipolar membrane migrate to the cathode chamber and the anode chamber respectively, causing drastic changes in the pH value of the anode and cathode solutions, thereby affecting the operating stability of the bipolar membrane electrode seawater hydrogen production device.
[0004] Therefore, considering the synergy between the cathode and anode catalysts and the water dissociation of the bipolar membrane, catalysts that can operate efficiently and stably in a larger pH range are more suitable for bipolar membrane seawater electrolysis devices. The catalysts currently used in bipolar membrane seawater electrolysis devices are mainly precious metal-based catalysts, the anode catalyst is mainly IrOx, and the cathode catalyst is mainly Pt. Precious metal-based catalysts have the problems of high cost, low natural abundance and poor stability. Non-precious catalysts have been reported in other seawater electrolysis hydrogen production systems, but there are few studies on non-precious metal catalysts for bipolar membrane seawater electrolysis hydrogen production devices.
[0005] Iron-cobalt-nickel layered hydroxide materials have excellent water electrolysis activity in a wide pH range. The ability to adapt to a wide range of electrolytes makes iron-cobalt-nickel layered hydroxides potentially suitable for bipolar membranes. However, the activity of iron-cobalt-nickel layered hydroxides as cathode catalysts in seawater electrolysis for hydrogen production is still poor and still needs further improvement.
[0006] The purpose of the present invention is to propose a hydrogen production device based on bipolar membrane electrolysis of seawater and to develop a novel bifunctional catalyst for hydrogen evolution at the cathode and oxygen evolution at the anode that is compatible with the device. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the problem that the electrodes for electrolyzing seawater are easy to precipitate and have poor operating stability, and to provide a device for electrolyzing seawater based on a bipolar membrane and a method for preparing an iron-cobalt-nickel-chromium oxide nanomaterial according to the ion transport characteristics of the bipolar membrane.
[0008] Among them, the iron-cobalt-nickel-chromium oxide nanomaterial has the characteristics of adapting to a wide range of pH values. The bipolar membrane can completely prevent chloride ions from penetrating into the anode chamber. The hydrogen ions generated by water dissociation in the membrane can inhibit the precipitation of calcium and magnesium ions in seawater. The synergistic effect of the iron-cobalt-nickel-chromium oxide nanomaterial and the bipolar membrane can make the electrolysis of seawater to produce hydrogen run stably. In addition, the iron-cobalt-nickel-chromium oxide nanomaterial used in the seawater electrolysis device is prepared by electrodeposition and calcination. The preparation method is simple and efficient. The obtained material can efficiently precipitate oxygen under alkaline conditions and efficiently precipitate hydrogen in simulated seawater. It can adapt to the pH value changes of the electrolyte in the seawater electrolysis device based on the bipolar membrane, thereby realizing the long-term stable operation of the reactor. In addition, since no precious metals are used, the cost is also lower.
[0009] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0010] A further object of the present invention is to provide a seawater electrolysis device based on a bipolar membrane.
[0011] A further object of the present invention is to provide a method for preparing iron-cobalt-nickel-chromium oxide nanomaterials.
[0012] A further object of the present invention is to provide the use of the above-mentioned iron-cobalt-nickel-chromium oxide nanomaterial as anode and cathode materials in a seawater electrolysis device.
[0013] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0014] A method for preparing an iron-cobalt-nickel-chromium oxide nanomaterial comprises the following steps:
[0015] S1. preparing a mixed solution containing iron, cobalt and nickel salts to obtain a precursor solution;
[0016] S2. The precursor solution is used as an electrolyte for an electrochemical deposition reaction to obtain an iron-cobalt-nickel layered hydroxide, and the nickel foam is cleaned before the electrodeposition;
[0017] S3. Soaking the iron-cobalt-nickel layered hydroxide material in a chromium salt solution, drying it and then calcining it to obtain an iron-cobalt-nickel-chromium oxide nanomaterial.
[0018] Preferably, the specific process of the cleaning in step S2 is: first, ultrasonically clean the nickel foam with hydrochloric acid for 10 to 25 minutes, then, ultrasonically clean the nickel foam with an inorganic solvent for 10 to 25 minutes, then, ultrasonically clean the nickel foam with deionized water for 10 to 25 minutes, and finally dry overnight.
[0019] Preferably, the inorganic solvent is acetone or ethanol, and the concentration of the hydrochloric acid is 1 to 3 mol / L.
[0020] More preferably, the drying temperature is 60-80°C.
[0021] Preferably, the size of the nickel foam in step S2 is 2×2 cm.
[0022] Preferably, the average pore size of the nickel foam in step S2 is 0.1-0.15 mm, and the porosity is 96%-97%.
[0023] Preferably, the solvent is water.
[0024] More preferably, the drying temperature is 60-80°C.
[0025] Preferably, the molar ratio of cobalt and nickel elements in the electroplating electrolyte in step S2 is 1:1:2.
[0026] Preferably, in the electrolyte, the volume ratio of the sum of the masses of the iron, cobalt and nickel sources to the solvent is (4-5) g:50 mL.
[0027] More preferably, the iron source is ferrous sulfate.
[0028] More preferably, the cobalt source is cobalt nitrate.
[0029] More preferably, the nickel source is nickel nitrate.
[0030] More preferably, the electrodeposition reaction is carried out in a three-electrode system.
[0031] More preferably, in the three-electrode system, the nickel foam in step S2 is the working electrode, the platinum wire electrode is the counter electrode, and the saturated calomel electrode is the reference electrode.
[0032] More preferably, the voltage used in the electrodeposition reaction is -1.0V.
[0033] More preferably, the electrodeposition reaction time is 10 to 25 minutes.
[0034] More preferably, the electrolytic solution for electrodeposition can carry out 1 to 6 times of electroplating reaction.
[0035] Preferably, the electrodeposition reaction in step S2 includes cleaning and drying steps.
[0036] More preferably, the drying temperature is 60-80°C.
[0037] Preferably, the concentration of chromium in the chromium-containing solution in step S3 is 0.05-0.2 mol / L.
[0038] More preferably, the chromium-containing solution is chromium nitrate solution.
[0039] Preferably, the soaking time in step S3 is 5 to 30 minutes.
[0040] Preferably, the soaking in step S3 includes washing and drying steps.
[0041] More preferably, the drying temperature is 30-50°C.
[0042] Preferably, the calcination temperature in step S3 is 300-500°C.
[0043] Preferably, the calcination time in step S3 is 2 to 4 hours.
[0044] An iron-cobalt-nickel-cobalt oxide nanomaterial is prepared by the above preparation method.
[0045] The use of the above-mentioned iron-cobalt-nickel-cobalt oxide nanomaterials as cathodes and anodes in the preparation of a bipolar membrane-based seawater electrolysis device is also within the protection scope of the present invention.
[0046] A seawater electrolysis device based on a bipolar membrane comprises a bipolar membrane, an anode, an anolyte, a cathode and a catholyte; the materials of the anode and the cathode are the above-mentioned iron-cobalt-nickel-cobalt oxide nanomaterials, the anolyte is 1M potassium hydroxide, and the catholyte is simulated seawater.
[0047] The iron-cobalt-nickel-chromium oxide nanomaterial of the present invention is used as anode and cathode materials, potassium hydroxide is used as anolyte, simulated seawater is used as cathode liquid, and bipolar membrane is used as diaphragm to construct a seawater electrolysis device based on a bipolar membrane. The Faraday efficiency of hydrogen and oxygen evolution of the seawater electrolysis device can exceed 90%. The reversely configured bipolar membrane seawater electrolysis device has better stability, while the seawater electrolysis device under the forward configuration requires a lower voltage.
[0048] Preferably, the concentration of the anolyte is 1M.
[0049] Preferably, the concentration of the cathode liquid is 33.1 g / L.
[0050] Preferably, the ion concentration of the simulated seawater is: Na + :0.9±0.2g·L -1 ,K + :0.35±0.03g·L -1 ,Ca 2+ :0.4±0.04g·L -1 Mg 2+ :1.2±0.12g·L -1 ,Cl - :1.8±0.9g·L -1 ,SO4 2- :2.2±0.2g·L -1 .
[0051] Preferably, the distance between the anode and the cathode is 0.5-1.0 cm.
[0052] Preferably, the forward configuration is that when constructing a seawater electrolysis device, the anion exchange layer of the bipolar membrane faces the cathode, and the cation exchange layer faces the anode.
[0053] Preferably, the reverse configuration is that the anion exchange layer of the bipolar membrane faces the anode, and the cation exchange layer faces the cathode.
[0054] Preferably, the hydrogen produced in the cathode chamber and the oxygen produced in the anode chamber of the seawater electrolysis device are collected by gas collection bags.
[0055] Preferably, the cathode liquid and the anode liquid are circulated under the action of a peristaltic pump.
[0056] More preferably, the flow rate of the peristaltic pump is 10 to 60 mL / min.
[0057] Preferably, the external voltage is provided by a DC power supply.
[0058] More preferably, the current density provided by the DC power supply is 10-600 mA / cm 2 .
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] (1) In the present invention, through a specific electrodeposition reaction, the iron source, the nickel source and the cobalt source can react on the nickel foam to form iron-cobalt-nickel layered hydroxide nanosheets, and then obtain the iron-cobalt-nickel-chromium oxide nanomaterial through a calcination reaction. The obtained material can undergo an oxygen evolution reaction in an alkaline environment, and at the same time, it also has good hydrogen evolution performance in simulated seawater. Therefore, the iron-cobalt-nickel-chromium oxide nanomaterial can be applied to a bipolar membrane-based seawater electrolysis device with large changes in electrolyte pH and conductivity, which is conducive to long-term stable operation. In addition, since this method does not use precious metals such as platinum, ruthenium, and iridium, the preparation process is simple and the cost is low.
[0061] (2) The iron-cobalt-nickel-chromium oxide nanomaterial of the present invention is used as an electrode material for a seawater electrolysis device based on a bipolar membrane, which can not only enable the seawater electrolysis device to achieve a Faraday efficiency of more than 90% for hydrogen and oxygen evolution. Since the iron-cobalt-nickel-chromium oxide nanomaterial can adapt to a wide range of pH values, and the bipolar membrane not only completely prevents chloride ions from penetrating into the anode chamber, but the hydrogen ions generated by water dissociation in the membrane can also inhibit the precipitation of calcium and magnesium ions in seawater. The synergistic effect of the catalyst and the bipolar membrane can enable the reactor to operate stably for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a schematic diagram of the structure of the bipolar membrane-based seawater electrolysis device of Example 2.
[0063] Figure 2 These are scanning electron microscope images of the iron-cobalt-nickel-chromium oxide nanomaterial of Example 1 at different magnifications.
[0064] Figure 3 This is the XRD diagram of the iron-cobalt-nickel-chromium oxide nanomaterial of Example 1.
[0065] Figure 4 These are the transmission electron microscope images and selected area electron diffraction images of the iron-cobalt-nickel-chromium oxide nanomaterial of Example 1.
[0066] Figure 5 This is a graph showing the test results of the iron-cobalt-nickel-chromium oxide nanomaterial of Example 1 in hydrogen evolution in simulated seawater electrolyte and oxygen evolution in alkaline electrolyte.
[0067] Figure 6 The voltage-current density curves of the bipolar membrane-based seawater electrolysis device of Examples 2 to 3 under different bipolar membrane configuration modes.
[0068] Figure 7 The voltage-current density curves of the bipolar membrane-based seawater electrolysis devices of Examples 4 to 12 are shown.
[0069] Figure 8 Graph showing the hydrogen evolution rate results of the bipolar membrane-based seawater electrolysis device of Examples 4 to 12.
[0070] Fig. 9 Graph showing oxygen evolution rate results of the bipolar membrane-based seawater electrolysis device of Examples 4 to 12.
[0071] Fig.10 This is a diagram showing the cell voltage variation of the bipolar membrane-based seawater electrolysis device of Examples 3 and 4 after running for 600 hours. DETAILED DESCRIPTION
[0072] The present invention is further described in detail below in conjunction with the accompanying drawings.
[0073] Example 1
[0074] This embodiment provides a method for preparing an iron-cobalt-nickel-chromium oxide nanomaterial, comprising the following steps:
[0075] 1. First, pre-treat the 2×2 cm nickel foam to remove grease and oxides on its surface: ultrasonically clean the nickel foam with an inorganic solvent, then ultrasonically clean it with hydrochloric acid, and finally ultrasonically clean it with deionized water for use.
[0076] The inorganic solvent is ethanol, the concentration of hydrochloric acid is 1 mol / L, and the ultrasonic cleaning time is 20 min.
[0077] 2. Preparation of iron-cobalt-nickel layered hydroxide nanomaterials by electrodeposition: Dissolve ferrous sulfate, nickel nitrate hexahydrate and cobalt nitrate hexahydrate in 50 mL of deionized water and stir for 10 min to obtain an electrolyte for electrodeposition. Then, use the pretreated nickel foam as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode to construct a three-electrode system and react at a voltage of -1.0 V for 20 min. After the reaction, rinse repeatedly with deionized water and dry to obtain iron-cobalt-nickel layered hydroxide.
[0078] 3. Prepare iron-cobalt-nickel-chromium oxide nanomaterials by calcination method: soak iron-cobalt-nickel layered hydroxide in chromium nitrate solution for 10 minutes, dry it, and calcine it in a muffle furnace at 400° C. for 3 hours to obtain iron-cobalt-nickel-chromium oxide nanomaterials.
[0079] Among them, the molar concentration ratio of ferrous sulfate, cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 1:1:2; the volume ratio of the sum of the masses of ferrous sulfate, cobalt nitrate hexahydrate and nickel nitrate hexahydrate to deionized water is 4.74g:50mL; the concentration of chromium nitrate solution is 0.1mol / L, the drying temperature is 60°C, and the drying time is 12h.
[0080] Example 2
[0081] The present embodiment provides a bipolar membrane-based seawater electrolysis device, which includes: an anode chamber, a cathode chamber, a bipolar membrane, an anolyte and a cathode solution contained in the anode chamber and the cathode chamber, and an anode arranged in the anode chamber and a cathode arranged in the cathode chamber.
[0082] The materials forming the main bodies of the anode chamber and cathode chamber are silicone gaskets and organic glass, and the materials of the anode and cathode are the iron-cobalt-nickel-chromium oxide nanomaterials prepared in Example 1; the anode liquid is 1M potassium hydroxide solution, and the cathode liquid is a simulated seawater solution.
[0083] The structure of the seawater electrolysis device based on bipolar membrane is as follows Figure 1 As shown, the anode is in direct contact with the anolyte, and the cathode is in direct contact with the catholyte. The anode chamber and the cathode chamber are separated by a bipolar membrane. The anion exchange layer of the bipolar membrane faces the anode, and the cation exchange layer faces the cathode. The anode and cathode are connected to a DC power supply through a titanium wire. The anode chamber and the cathode chamber are both cylinders with a diameter of 3 cm and a volume of about 9.8 mL. The effective area of the anode and cathode is 4 cm 2 , with a spacing of 1 cm between them. The volume of the cathode liquid and the anode liquid were 100 mL respectively, and the electrolyte circulation was achieved by a peristaltic pump. The current of the DC power supply was set to 0.08 A, and the current density on the electrode was 20 mA / cm 2 The flow rate of the peristaltic pump was set to 20 mL / min. The generated gas was collected by a gas sampling bag.
[0084] Example 3
[0085] This embodiment provides a seawater electrolysis device based on a bipolar membrane, which is basically the same as the device in Example 2, except that the anion exchange layer of the bipolar membrane faces the cathode, and the cation exchange layer faces the anode.
[0086] Example 4
[0087] This embodiment provides a seawater electrolysis device based on a bipolar membrane, which is basically the same as the seawater electrolysis device of Example 2, except that the anode material is a titanium mesh and the cathode material is a titanium mesh.
[0088] Example 5
[0089] This embodiment provides a seawater electrolysis device based on a bipolar membrane, which is basically the same as the seawater electrolysis device of Example 2, except that the anode material is a titanium mesh and the cathode material is an iron-cobalt-nickel-chromium oxide nanomaterial.
[0090] Example 6
[0091] This embodiment provides a seawater electrolysis device based on a bipolar membrane. The configuration of the device is basically the same as that of the seawater electrolysis device in Example 4, except that the current density is set to 100 mA / cm 2 .
[0092] Example 7
[0093] This embodiment provides a seawater electrolysis device based on a bipolar membrane. The configuration of the device is basically the same as that of the seawater electrolysis device in Example 5, except that the current density is set to 100 mA / cm 2 .
[0094] Example 8
[0095] This embodiment provides a seawater electrolysis device based on a bipolar membrane. The configuration of the device is basically the same as that of the seawater electrolysis device in Example 6, except that the current density is set to 100 mA / cm 2 .
[0096] Example 9
[0097] This embodiment provides a seawater electrolysis device based on a bipolar membrane. The configuration of the device is basically the same as that of the seawater electrolysis device in Example 4, except that the current density is set to 500 mA / cm 2 .
[0098] Example 10
[0099] This embodiment provides a seawater electrolysis device based on a bipolar membrane. The configuration of the device is basically the same as that of the seawater electrolysis device in Example 5, except that the current density is set to 500 mA / cm 2 .
[0100] Embodiment 11
[0101] This embodiment provides a seawater electrolysis device based on a bipolar membrane. The configuration of the device is basically the same as that of the seawater electrolysis device in Example 6, except that the current density is set to 500 mA / cm 2 .
[0102] Performance Testing
[0103] 1. Characterization of morphology and material composition
[0104] The iron-cobalt-nickel-chromium oxide nanomaterial obtained in Example 1 was subjected to electron microscope scanning. The results are as follows: Figure 2 As shown, Figure 2 (A) and (B) are scanning electron microscope images of iron, cobalt, nickel and chromium oxide nanomaterials at different magnifications. Figure 2 (A) It can be seen that the iron-cobalt-nickel-chromium oxide material appears as uniform micron spheres distributed on the nickel foam substrate; Figure 2 (B) It can be seen that the iron-cobalt-nickel-chromium oxide nanomaterial presents a nanosheet structure. The iron-cobalt-nickel-chromium oxide nanomaterial of Example 1 was subjected to X-ray diffraction (XRD) analysis, and the results are as follows: Figure 3 As shown. Figure 3 It can be seen that the XRD pattern of the iron-cobalt-nickel-chromium oxide material shows (003), (006), (012) and (0015) crystal planes (JCPDS No.51-0463). The (111), (220), (311), (222), (400), (422), (511) and (440) crystal planes correspond to the diffraction peaks of the iron-cobalt-nickel-chromium oxide nanomaterial.
[0105] The iron-cobalt-nickel-chromium oxide nanomaterial obtained in Example 1 was characterized by transmission electron microscopy. Figure 4 Consistent with the SEM images, the TEM images also show a two-dimensional nanostructure of FeCoNiCr oxide ( Figure 4 (A)). The lattice fringe spacing is 0.246nm and 0.204nm, corresponding to the (311) and (400) crystal planes of FeCoNiCr oxide, respectively. Figure 4 (B)). Selected area electron diffraction pattern ( Figure 4 (C) shows the diffraction rings of the (220), (222) and (400) crystal planes of the FeCoNiCr oxide nanomaterial, which is consistent with the XRD results, indicating that the material was successfully synthesized. The two-dimensional nanosheet structure of the FeCoNiCr oxide nanomaterial has a large specific surface area, which can increase the contact area between the catalyst and the electrolyte, thereby accelerating the interfacial reaction.
[0106] 2. Electrochemical performance test
[0107] The iron-cobalt-nickel-chromium oxide nanomaterials obtained in Example 1 were placed in a three-electrode system to test their hydrogen and oxygen evolution performances. The results are as follows: Figure 5 shown. Figure 5 This is the result of linear voltammetric scanning analysis. Figure 5 (A) It can be seen that in simulated seawater, the Fe-Co-Ni-Cr oxide nanomaterial can obtain 10 mA cm at a voltage of -0.11 V (vs. RHE). -2 The current density of the Fe-Co-Ni-Cr oxide nanomaterials is about 10 mA cm-1, while the nickel foam requires 0.25 V (vs. RHE). For the oxygen evolution reaction, when 1 M potassium hydroxide is used as the electrolyte, the Fe-Co-Ni-Cr oxide nanomaterials have a current density of about 10 mA cm-1. -2 The oxygen evolution overpotential is 78mV ( Figure 5 (B)). Therefore, the Fe-Co-Ni-Cr oxide nanomaterials have good hydrogen and oxygen evolution properties.
[0108] The bipolar membrane-based seawater electrolysis device of Examples 2 to 3 using the iron-cobalt-nickel-chromium oxide nanomaterials obtained in Example 1 as cathode and anode was operated at 20 mA·cm in different bipolar membrane configurations. -2 The stability test of Figure 6 The reverse configuration mode of the bipolar membrane electrolysis device of Example 2 is to obtain 20mA·cm -2 The current density requires 2.82V, while the device with the forward bipolar membrane configuration only requires 2.11V, which shows that both bipolar membrane configurations can be used for seawater electrolysis. The forward bipolar membrane configuration can reduce the applied voltage, but the electrolyzer voltage increases over time. This may be because, in the forward mode, the pH value of the cathode liquid will gradually increase, causing the calcium and magnesium ions in the simulated seawater to precipitate on the electrode surface, blocking the active sites and increasing the electrolyzer voltage. In the reverse mode, the hydrogen ions produced by the dissociation of water in the bipolar membrane migrate to the cathode chamber, which can maintain the pH value of the cathode liquid from rising, and thus the reactor operates stably. Therefore, Examples 3 to 12 all adopt the reverse configuration mode ( Figures 5 to 10 ).
[0109] When both the cathode and cathode are titanium mesh (Examples 2, 4 and 5), at 20 mA·cm -2 At a current density of , the cell voltage is 2.66 V and the hydrogen evolution rate is 1.44 mmol·h -1 , oxygen evolution rate is 0.76mmol·h -1 ; at 100mA·cm -2 At a current density of , the cell voltage is 3.49 V and the hydrogen evolution rate is 8.32 mmol·h -1 , oxygen evolution rate is 3.67mmol·h -1 ; at 500mA·cm -2 At a current density of , the cell voltage is 7.56 V and the hydrogen evolution rate is 36.39 mmol·h -1 , oxygen evolution rate is 18.17mmol·h -1 .
[0110] When both the cathode and cathode are made of iron-cobalt-nickel-chromium oxide nanomaterials (Examples 6-8), at 20 mA·cm -2 At a current density of , the cell voltage is 2.7 V and the hydrogen evolution rate is 1.48 mmol·h -1 , oxygen evolution rate is 0.74mmol·h -1 ; at 100mA·cm -2 At a current density of , the cell voltage is 3.72 V and the hydrogen evolution rate is 7.42 mmol·h -1 , oxygen evolution rate is 3.66mmol·h -1 ; at 500mA·cm -2At a current density of , the cell voltage is 7.3 V and the hydrogen evolution rate is 37.22 mmol·h -1 , oxygen evolution rate is 19.29mmol·h -1 .
[0111] When the anode is titanium mesh and the cathode is iron-cobalt-nickel-chromium oxide nanomaterial (Examples 9-11), at 20 mA·cm -2 At a current density of , the cell voltage is 2.7 V and the hydrogen evolution rate is 1.48 mmol·h -1 , oxygen evolution rate is 0.74mmol·h -1 ; at 100mA·cm -2 At a current density of , the cell voltage is 4.14 V and the hydrogen evolution rate is 7.24 mmol·h -1 , oxygen evolution rate is 3.71mmol·h -1 ; at 500mA·cm -2 At a current density of , the cell voltage is 8.95 V and the hydrogen evolution rate is 36.93 mmol·h -1 , oxygen evolution rate is 18.42mmol·h -1 .
[0112] The seawater electrolysis devices of Example 2 and Example 4 were subjected to a 600-hour stability test ( Fig.10 ). From the results, it can be seen that the bipolar membrane is reversely assembled at 20 mA·cm -2 At a current density of , both electrodes can operate stably, and the cell voltage is stable at 2.49V and 2.82V respectively. In addition, the cell voltage of the bipolar membrane electrolysis seawater device using iron-cobalt-nickel-chromium oxide nanomaterials as electrodes is lower than that of the titanium mesh during long-term operation. The average hydrogen and oxygen evolution rates of Example 2 and Example 4 during the 600h operation process are 1.43 and 1.46 mmol·h respectively. -1 and 0.72, 0.73 mmol·h -1 .
[0113] In conclusion, Fe-Co-Ni-Cr oxide nanomaterials can be applied to seawater electrolysis devices based on bipolar membranes, with low cell voltage and stable operation.
[0114] The present invention and its embodiments are described above, and such description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.
Claims
1. A method for preparing an iron-cobalt-nickel-chromium oxide nanomaterial, characterized in that: The steps include: S1. preparing a mixed solution containing iron, cobalt and nickel salts to obtain a precursor solution; S2. using the precursor solution as an electrolyte for an electrochemical deposition reaction to obtain an iron-cobalt-nickel layered hydroxide; S3. Soaking the iron-cobalt-nickel layered hydroxide material in a chromium salt solution, drying it and then calcining it to obtain an iron-cobalt-nickel-chromium oxide nanomaterial.
2. The method for preparing an iron-cobalt-nickel-chromium oxide nanomaterial according to claim 1, characterized in that: The nickel salt in S1 is nickel nitrate, the cobalt salt is cobalt nitrate, and the iron salt is ferrous sulfate; in the mixed solution, the molar ratio of iron, cobalt and nickel elements is 1:1:2, and the volume of the electrolyte is 50 mL; The volume ratio of the sum of the masses of the iron, cobalt and nickel sources to the solvent is (4-5) g:50 mL, and the electrolyte is used 1 to 6 times.
3. The method for preparing an iron-cobalt-nickel-chromium oxide nanomaterial according to claim 1, characterized in that: In the electrochemical deposition reaction of S2, the working electrode is nickel foam, the counter electrode is a platinum wire electrode, the reference electrode is a saturated calomel electrode, the electrodeposition voltage is -1.0V, and the deposition time is 10 to 25 minutes; The nickel foam is cleaned before the electrodeposition, wherein the size of the nickel foam is 2×2 cm, the average pore diameter is 0.1-0.15 mm, and the porosity is 96%-97%.
4. The method for preparing an iron-cobalt-nickel-chromium oxide nanomaterial according to claim 3, characterized in that: The first cleaning of the nickel foam in S2 includes: The nickel foam is ultrasonically cleaned with hydrochloric acid for 10 to 25 minutes, then with an inorganic solvent for 10 to 25 minutes, then with deionized water for 10 to 25 minutes, and finally dried overnight; The inorganic solvent is acetone or ethanol, the concentration of hydrochloric acid is 1-3 mol / L, and the drying temperature is 60-80°C.
5. The method for preparing an iron-cobalt-nickel-chromium oxide nanomaterial according to claim 1, characterized in that: The chromium salt in S3 is chromium nitrate, the concentration is 0.05-0.2 mol / L, the solution volume is 50 mL, the soaking time is 5-30 min, and the soaking is completed and then cleaned and dried.
6. The method for preparing an iron-cobalt-nickel-chromium oxide nanomaterial according to claim 1 or 5, characterized in that: In the S3, the calcination temperature is 300-500° C., and the calcination time is 2-4 hours.
7. An iron-cobalt-nickel-chromium oxide nanomaterial, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 5.
8. Use of the iron-cobalt-nickel-chromium oxide nanomaterial according to claim 7 as cathode and anode in the preparation of a seawater electrolysis device.
9. A seawater electrolysis device based on a bipolar membrane, characterized in that: It comprises an anode, a bipolar membrane, a cathode and an electrolyte; the materials of the anode and the cathode are the iron-cobalt-nickel-chromium oxide nanomaterials as claimed in claim 8, the distance between the anode and the cathode is 0.5 to 1.0 cm, and the electrolyte is potassium hydroxide and simulated seawater.
10. The seawater electrolysis device according to claim 9, characterized in that: The potassium hydroxide concentration is 0.5-3 mol / L, and the simulated seawater is prepared from 33.1 g / L of sea salt.
Citation Information
Patent Citations
Preparation method of trimetal double hydroxide hollow nanocage oxygen evolution electrocatalyst
CN112264021A
Preparation method of high-activity difunctional oxygen electrocatalyst
CN113502487A
Method for preparing high-performance catalyst by using chromium ion pollutants in surface water
CN115948762A
Iron-cobalt-nickel nano material, water electrolysis hydrogen production device and preparation method and application of iron-cobalt-nickel nano material
CN115976592A
Bifunctional catalytic electrode for producing hydrogen by electrolyzing seawater as well as preparation method and application of bifunctional catalytic electrode
CN116752181A